Dual pharmacological inhibitor of endocannabinoid degrading enzymes reduces depressive-like behavior in female rats. (January 2020) - Dong, Bin; Shilpa, Borehalli M.; Shah, Relish; Goyal, Arjun; Xie, Shan; Bakalian, Mihran J.; Suckow, Raymond F.; Cooper, Thomas B.; Mann, J. John; Arango, Victoria; Vinod, K. Yaragudri
Abstract: Major depressive disorder (MDD) is common, often under-treated and a leading cause of disability and mortality worldwide. The causes of MDD remain unclear, including the role of the endocannabinoid system. Intriguingly, the prevalence of depression is significantly greater in women than men. In this study we examined the role of endocannabinoids in depressive behavior. The levels of endocannabinoids, N-arachidonoyl ethanolamide (AEA) and 2-arachidonoyl glycerol (2-AG) were measured along with brain derived neurotrophic factor (BDNF) in postmortem ventral striata of female patients with MDD and non-psychiatric controls, and in Wistar Kyoto (WKY) rat, a selectively inbred strain of rat widely used for testing the depressive behavior. The effect of pharmacological elevation of endocannabinoids through inhibition of their catabolizing enzymes (fatty acid amide hydrolase [FAAH] and monoacyl glycerol lipase [MAGL]) on depressive-like phenotype was also assessed in WKY rat. The findings showed lower levels of endocannabinoids and BDNF in the ventral striata of MDD patients and WKY rats. A dual inhibitor of FAAH and MAGL, JZL195, elevated the endocannabinoids and BDNF levels in ventral striatum, and reduced the depressive-like phenotype in female WKY rats. Collectively, our study suggests a blunted ventral striatal endocannabinoid and BDNF signaling in depressive behavior and concludes that endocannabinoid enhancing agents may have an antidepressant effect.